RELATIONSHIP OF OWNERSHIP STRUCTURE AND ACCOUNTING CONSERVATISM IN THE MANUFACTURING INDUSTRIAL SECTOR COMPANIES LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2011 - 2013 - Yan Christianto Setiawan (Jurnal Akuntansi, 2020)
In 2002, McKinsey & Co. conducted a survey whose results stating that investors tend to avoid companies with a bad predicate in corporate governance. Financial statements is one of the important instruments in achieving good corporate governance. The quality of the financial statements can be viewed through the characteristics adopted by the financial statements. One of these characteristics is accounting conservatism. Conservatism as a facility that can improve the efficiency of the contract between the principal agent, certainly strongly influenced by whom and how many the owner (principal) of the company. This study aims to examine the relationship of ownership structure and accounting conservatism. In this study, the population used is the entire business entity engaged in the manufacturing sector and listed on the Indonesia Stock Exchange (BEI) in the period 2011 - 2013. The sampling technique in this study using purposive / judgment. This test uses regression techniques fixed effect panel data structure. The results of this study show that (1) there is a positive relationship between the largest shareholder or controlling shareholder and accounting conservatism (2) there is a positive relationship between the family as the largest shareholder as well as the controlling shareholder and accounting conservatism (3) there was no correlation between non-family as the largest shareholder and accounting conservatism, but there is a negative relationship when nonfamily become the controlling shareholder and accounting conservatism (4) the presence of unrelated blockholder significantly to reduce the preferences of the largest shareholder and accounting conservatism on the whole sample or sub-sample of nonfamily , but there is a negative correlation in the sub samples when the family became the largest shareholder. Keywords : conservatism, corporate governance, ownership structure.